In-vitro Chemodissolution of Urinary Stones by Some Chelating Natural Acids - Rao, T.V.R.K.; Bano, Sofia (Asian Journal of Chemistry, 2012)
Chemodissolution of ten surgically removed urinary stones was studied in dilute aqueous solutions of some chelating natural acids, viz., lactic, malic, tartaric, citric or succinic acid. All the stones studied were of pure oxalate or phosphate or mixed oxalate-phosphate types. Kinetics of dissolution was observed over a period of ten days. Results revealed significant in-vitro solubility of urinary stones in the natural acids. Surface activity and chelation specificity seem to be the dominant factors in the process of dissolution.